The routledge research companion to nineteenth-century British literature and science (Routledge, 2017)
Tracing the continuities and trends in the complex relationship between literature and science in the long nineteenth century, this companion provides scholars with a comprehensive, authoritative and up-to-date foundation for research in this field. In intellectual, material and social terms, the transformation undergone by Western culture over the period was unprecedented. Many of these changes were grounded in the growth of science. Yet science was not a cultural monolith then any more than it is now, and its development was shaped by competing world views. To cover the full range of literary engagements with science in the nineteenth century, this companion consists of twenty-seven chapters by experts in the field, which explore crucial social and intellectual contexts for the interactions between literature and science, how science affected different genres of writing, and the importance of individual scientific disciplines and concepts within literary culture. Each chapter has its own extensive bibliography. The volume as a whole is rounded out with a synoptic introduction by the editors and an afterword by the eminent historian of nineteenth-century science Bernard Lightman.